The Effect of Weight-Loss Interventions on Cervical and Chin Subcutaneous Fat Depots; the CENTRAL Randomized Controlled Trial - Gal Tsaban (MDPI AG, 2021)
Accumulation of cervical and chin subcutaneous adipose tissues (SAT) represent known phenotypes of obesity. We aimed to evaluate the sensitivity of these fat storages to long-term weight-loss directed lifestyle-intervention and to assess their relations to bodily-adiposity, insulin-resistance, and cardiometabolic risk; We randomly assigned 278 participants with abdominal-obesity/dyslipidemia to low-fat or Mediterranean/low-carbohydrate diets +/− physical-activity. All participants underwent an 18 month whole-body magnetic resonance imaging follow-up, from which we assessed cervical and chin SAT-areas; Participants (age = 48 years; 90% men; body-mass-index = 30.9 kg/m2) had an 18-month adherence-rate of 86%. Cervical-SAT and chin-SAT decreased after 6-months (−13.1% and −5.3%, respectively, p < 0.001). After 18-months only cervical-SAT remained decreased compared to baseline (−5%, p < 0.001). Cervical and chin-SAT 18-month changes were associated with changes in weight (r = 0.70, r = 0.66 respectively; <0.001 for both) and visceral-adipose-tissue (VAT; r = 0.35, r = 0.42 respectively; <0.001 for both). After adjustment to VAT, waist-circumference, or weight-changes, chin-SAT 18-month reduction was associated with favorable changes in fasting-glucose (β = 0.10; p = 0.05), HbA1c (β = 0.12; p = 0.03), and homeostasis-model-assessment-of-insulin-resistance (β = 0.12; p = 0.03). Cervical-SAT 18-month reduction was associated with decreased triglycerides (β = 0.16; p = 0.02) and leptin (β = 0.19; p = 0.01) independent of VAT; Cervical and chin-SATs are dynamic fat depots that correspond with weight-loss and are associated with changes in cardiometabolic profile. In long-term, chin-SAT displays a larger rebound compared with cervical-SAT. Chin-SAT accumulation is associated with in insulin-resistance, independent of central obesity. (ClinicalTrials identifier NCT01530724)